Targeting the inhibitors of apoptosis proteins (IAPs) to combat drug resistance in cancers - Ye, Qingmei; Zhuang, Xiao-Zhao; Li, Juan; Zhou, Xin (Frontiers in Pharmacology, 2025)
Inhibitors of Apoptosis Proteins (IAPs) are a family of anti-apoptotic proteins that play a pivotal role in apoptosis in general but also as oncoproteins in cancer progression and, more importantly, drug resistance. IAPs enable cancer cells to evade programmed cell death and adapt to therapeutic stress by inhibiting pro-apoptotic caspase activity as well as modulating pivotal survival pathways. Recent advancements in targeting IAPs, particularly through the use of SMAC (second mitochondria-derived activator of caspase) mimetics and other small-molecule antagonists or inhibitors, have opened new avenues for overcoming drug resistance in cancers. The current review attempted to summarize the status quo of IAPs’ role in promoting chemotherapeutic drug resistance in various cancer treatments and discuss the most recent development of IAP-targeting therapies, particularly small-molecule inhibitors including their combinational strategies to enhance the sensitivity or achieve synergism to existing therapeutics. Additionally, we also outline the challenges and offer future perspectives for optimizing IAP-targeted approaches to improve clinical outcomes.